Study on Location Plan of Temporary Shelter for Tsunami Disaster in Kuta Bay of Central Lombok - Adi Mawardin (Journal of the Civil Engineering Forum, 2018)
Historical record showed in 1977, tsunami attacked Lombok and caused extensive damages due to tectonic activity. Kuta Bay located in the southern area of Lombok has a high risk of earthquake and tsunami, thus mitigation plan on tsunami attack is very important. This study aimed to determine the arrival time, run-up height of tsunami and the coverage areas, so it could be used to determine the temporary shelter location (Tempat Evakuasi Sementara-TES). Simulation of the tsunami wave propagation used the TUNAMI modified (beta version) program with three scenarios of earthquake magnitude variation (Mw), namely 7.7, 8.1, 8.3, and 7.9 (based on the Sumba earthquake event in 1977). Field surveys, questionnaire distributions, and interviews were used in determining input parameters of Tsunami Evacuation Simulation (Simulasi Evakuasi Tsunami-SET) by using 2011 EVACUWARE 1.0 version. Tsunami wave propagation simulation showed the tsunami arrival time on Kuta Bay ranged between 21 - 38 minutes. Tsunami run-up height was about 1.01 - 8.71 meters along Kuta Bay, with the farthest distance of inundation was 860 meters from the seashore. The percentage of survivors based on SET results in scenario 1 and 2 for 20 minutes of evacuation time were respectively, 63.62% and 93.27%.